SPE International Symposium on Oilfield Chemistry 2015
DOI: 10.2118/173745-ms
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Behavior and Proppant Transport Properties of a New High-Temperature Viscoelastic Surfactant-Based Fracturing Fluid

Abstract: Viscoelastic surfactant (VES) fracture fluids were developed as a nondamaging alternative to conventional polymer-based fluids. However, the viscosity performance of typical VES fluids is dramatically reduced at high temperature. Therefore, these fluids are typically limited to treat relatively lowtemperature formations unless foamed with nitrogen or carbon dioxide. Recent laboratory work has shown that viscosity alone may not accurately assess proppant transport. Thus, combination of rotational and oscillator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Examples of cationic, nonionic, zwitterionic, and anionic surfactants have all been used for hydraulic-fracturing applications primarily in aqueous systems, although some examples of gelled hydrocarbon systems have been reported (Samuel 2009;Samuel et al 2014). Beginning with cationic surfactants, early studies of quaternary ammonium salts established their viscoelastic properties (Gravsholt 1976). Solutions that incorporate water, a water-soluble salt (electrolyte), and a quaternary ammonium salt have been used for drilling fluids, completion fluids, and hydraulic-fracturing fluids ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of cationic, nonionic, zwitterionic, and anionic surfactants have all been used for hydraulic-fracturing applications primarily in aqueous systems, although some examples of gelled hydrocarbon systems have been reported (Samuel 2009;Samuel et al 2014). Beginning with cationic surfactants, early studies of quaternary ammonium salts established their viscoelastic properties (Gravsholt 1976). Solutions that incorporate water, a water-soluble salt (electrolyte), and a quaternary ammonium salt have been used for drilling fluids, completion fluids, and hydraulic-fracturing fluids ).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of G 0 and G 00 can be used to determine whether a fluid is viscoelastic at a given temperature. A simple observational technique has also been described for determining whether a fluid is viscoelastic (Gravsholt 1976): Bubbles that appear during swirling of a sample will recoil when the swirling stops if the solution is viscoelastic.…”
Section: Surfactant Moleculementioning
confidence: 99%
“…A fracturing uid with good suspension properties is an effective way to ensure transport of a proppant to a fracture formation, and achieve high conductivity. [53][54][55] Fig. 15 shows the results of static proppant suspension tests, where BSP (0.5% BS + 0.5% CG, pH ¼ 10) fracturing uid with 30% of proppant was poured into a 100 mL in a measuring cylinder, and then heated to 65 C, and Fig.…”
Section: Proppant Suspension Measurementsmentioning
confidence: 99%
“…Some attempts have been made in this direction for particle-free polymer solutions, however, not in the context of hydraulic fracturing, and for very basic geometrical shapes of the channel [14,15]. Fluid elasticity specifically alters the sedimentation and rotation rate of a particle, which in turn causes different cross-stream flow-induced migration behaviors, affecting the overall particle transport efficiency [15][16][17][18]. There is still a need to fully understand how to tune the properties of polymeric fluids to efficiently transport particles.…”
Section: Introductionmentioning
confidence: 99%
“…The model introduced by Stokes, however, only accounted for the shear viscosity of the fluid, and required other correction factors to be suitable under different flow conditions or fluid types. In a series of works [17,27,28], Gomma et al showed that the effective shear viscosity is not the only factor to design efficient particle transport, and the fluid elasticity, quantified via the shear modulus, also plays a significant role. Several researchers [1,23,[29][30][31][32]] conducted comprehensive experimental and numerical investigations to determine the effect of fluid elasticity on the terminal velocity of a single sphere settling in a non-Newtonian elastic fluid in order to quantify the drag coefficient.…”
Section: Introductionmentioning
confidence: 99%